Entry strategies for international markets - Root, Franklin R. (San Francisco, 1998)
"The North American Free Trade Agreement, the new European common market, and the opening of Eastern Europe--among other recent geopolitical developments--have created unprecedented opportunities for American companies seeking to enter foreign markets. This guide offers executives practical advice, recently updated and expanded, on deciding which markets to enter, choosing a product for international distribution, designing an entry strategy, and developing an effective international marketing plan."